Proposta de uma metodologia de avaliação de investimentos em ativos de TI no setor público - Vidal, Ricardo da Rocha Duarte Lira (Universidade do Vale do Rio dos Sinos, 2018)
This study aims to create a methodological proposal for the evaluation of investments in Information Technology assets related to the public management sector through the collection and compilation of techniques, methods and tools for this purpose. It is a concept research that can support the decision-making process about whether or not to invest in IT projects, seeking to base and aggregate transparency on the actions of government agencies, proposing the creation of standards and making documentation available on taken decisions. Even though the initial focus is on public management actions, the methodology proposed here is not limited to this sector, and its application can be extended to the private sector environment. In this context of execution of the decision-making process, management concepts are sought, trying to add quality to the delivered services, qualifying the decisions about the investments that can be made in projects of creation and updating of information environment. During the development of this research there was interaction with public service agents, raising requirements to be met and starting from these definitions, the search for theoretical references was made to support the analysis proposals, studying methodologies, tools and techniques directed to the decision-making process . It was defined the way of construction of the analyzes by applying the steps of the Design Science Research (DSR) methodology, constructing artifacts from the theories compiled, providing the materialization of the actions through the use of the flows and drawn drawings, creating, a methodological process that supports the decision to execute the investment and also standardizes, documents and adds agility to its development.
Keywords: Metodologia de avaliação; Padronização de processos; Processo decisório; Decisão sobre investimento; Documentação de processos; Transparência de gestão pública; Evaluation methodology; Standardization of processes; Decisional process; Investment decision; Process documentation; Public management transparency; ACCNPQ::Ciências Sociais Aplicadas::Administração